A Smart Novel Approach of Blood Glucose Monitoring System using Arduino Board - G. S., Monisha; K., Kajendran; Nirmala, G.; D. R., Thirupurasundari (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A noninvasive blood glucose measuring method, where use of Near Infrared Technique that uses light transmission and absorption to measure blood glucose level accurately instead of traditional invasive method which include finger pricking which is painful and have risk of infection. Along with glucose level this can also give temperature and heart rate measurements. Also the measured result is transferred to the server which can be analyzed and the final report along with the suggestion and remedies are intimated to users. Diabetes is type of condition affecting the pancreas, which makes the hormone insulin, is diabetes. Diabetes results in a body's improper use of pancreatic insulin or the pancreas' inability to produce insulin. Produces, excessive blood glucose levels can occur. However, since glucose gives the body the energy it needs to function, the human body does need some of it. The prevalence of diabetes, which was 8% in 2011, is expected to rise to 10%. Monitoring blood glucose levels is essential for diabetes mellitus patients who want to regulate their glycemia. In order to prevent this, people must perform capillary tests at least three times per day and an additional laboratory test once or twice per month. In order to measure the amount of glucose using these traditional methods, patients must prick their fingertips. which is difficult for them to do, unsettling and unpleasant It is astonishing to realize that low- or middle-income countries account for 90% of diabetes cases.